2010
DOI: 10.1186/1746-1340-18-34
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of chiropractic use among older adults in the United States

Abstract: BackgroundLongitudinal patterns of chiropractic use in the United States, particularly among Medicare beneficiaries, are not well documented. Using a nationally representative sample of older Medicare beneficiaries we describe the use of chiropractic over fifteen years, and classify chiropractic users by annual visit volume. We assess the characteristics that are associated with chiropractic use versus nonuse, as well as between different levels of use.MethodsWe analyzed data from two linked sources: the basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 22 publications
1
51
1
Order By: Relevance
“…These findings are consistent with a number of studies that have looked at these 2 geographic measures independently. 4,11,13,14,26 However, our results indicate that the chiropractic prevalence across the urban-rural continuum varies significantly depending on the region of the country. In the Northeast, individuals living in small metropolitan areas have the highest rates of use.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…These findings are consistent with a number of studies that have looked at these 2 geographic measures independently. 4,11,13,14,26 However, our results indicate that the chiropractic prevalence across the urban-rural continuum varies significantly depending on the region of the country. In the Northeast, individuals living in small metropolitan areas have the highest rates of use.…”
Section: Discussioncontrasting
confidence: 64%
“…This estimate is considerably lower than estimates reported specifically for chiropractic use in the 1990s and is in line with a recent study looking at chiropractic use in the older US population. 1,2,5,11 We observed that the propensity to use these services varies by person-level sociodemographic and geographic characteristics and to a lesser extent by health characteristics. Race/ethnicity is a key demographic factor in characterizing the propensity for using chiropractic care.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4,5 For younger Medicare beneficiaries chiropractic prevalence rates are closer to national rates, ranging between 6%–7%. 6 While informative, these estimates are not reflective of the population that commonly seeks care from doctors of chiropractic (DCs)—namely, persons seeking treatment for spine-related health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7]9,15,16,[26][27][28][29] In many instances, whites used chiropractic at least twice as often as blacks. 2,4,6,7,9,15,16,26,29 Some have attributed this difference to the perception of discrepancies of health care treatment by blacks, lower average educational levels of blacks compared to whites, and the lack of accessibility to doctors of chiropractic (DCs) in black communities. 2,4,20,21,30 Very little information currently exists in the literature that describes use of chiropractic by non-Hispanic black patients.…”
Section: Introductionmentioning
confidence: 99%